Combining multi-scale 3D printing technologies to engineer reinforced hydrogel-ceramic interfaces - Diloksumpan, Paweena; de Ruijter, Mylène; Castilho, Miguel; Gbureck, Uwe; Vermonden, Tina; van Weeren, P René; Malda, Jos; Levato, Riccardo (IOP Publishing Ltd., 2020)
Multi-material 3D printing technologies that resolve features at different lengths down to the microscale open new avenues for regenerative medicine, particularly in the engineering of tissue interfaces. Herein, extrusion printing of a bone-biomimetic ceramic ink and melt electrowriting (MEW) of spatially organized polymeric microfibres are integrated for the biofabrication of an osteochondral plug, with a mechanically reinforced bone-to-cartilage interface. A printable physiological temperature-setting bioceramic, based on α-tricalcium phosphate, nanohydroxyapatite and a custom-synthesized biodegradable and crosslinkable poloxamer, was developed as bone support. The mild setting reaction of the bone ink enabled us to print directly within melt electrowritten polycaprolactone meshes, preserving their micro-architecture. Ceramic-integrated MEW meshes protruded into the cartilage region of the composite plug, and were embedded with mechanically soft gelatin-based hydrogels, laden with articular cartilage chondroprogenitor cells. Such interlocking design enhanced the hydrogel-to-ceramic adhesion strength >6.5-fold, compared with non-interlocking fibre architectures, enabling structural stability during handling and surgical implantation in osteochondral defects ex vivo. Furthermore, the MEW meshes endowed the chondral compartment with compressive properties approaching those of native cartilage (20-fold reinforcement versus pristine hydrogel). The osteal and chondral compartment supported osteogenesis and cartilage matrix deposition in vitro, and the neo-synthesized cartilage matrix further contributed to the mechanical reinforcement at the ceramic-hydrogel interface. This multi-material, multi-scale 3D printing approach provides a promising strategy for engineering advanced composite constructs for the regeneration of musculoskeletal and connective tissue interfaces.
Keywords: biofabrication; bioinspired interface; bone and cartilage tissue engineering; ceramics; melt electrowriting; microfibres; Bioengineering; Biochemistry; Biotechnology; Biomedical Engineering; Biomaterials; Research Support, Non-U.S. Gov't; Journal Article